PENGOLAHAN SUSU SAPI MELALUI PEMBUATAN YOGHURT PADA KELOMPOK TERNAK HARAPAN BARU M3 SAIYO DI KOTA PADANG PANJANG - Zulkarnaini Zulkarnaini; Eka Faradilla Hasanah; Shinta Silvia; Tivany Edwin; Rinda Andhita Regia; Desto Jumeno (Jurnal Hilirisasi IPTEKS, 2023)
The production and marketing of cow's milk owned by dairy farmers Harapan Baru M3 Saiyo experienced several problems, such as low selling prices and perceptions of cow's milk that the smell of cows is not liked by the public and milking which is still done manually which is considered less hygienic. This activity aims to educate the Silaing Atas Village, Padang Panjang City community, to process milk from local cattle farms. This activity was carried out in the Silaing Atas Village, KB Village, Batu Limo Tourism Object, Padang Panjang Regency. The exercise targets women and youth in the Silaing Atas Village, Padang Panjang City. The activities carried out included counseling and training on making yogurt based on dairy cow's milk belonging to the Harapan Baru M3 Saiyo farm. Sixty participants attended this activity. The participants were very enthusiastic about this yogurt-making training and counseling activity. The results of this yogurt-making activity benefitted the people of Padang Panjang city in supporting a healthy lifestyle. This activity can increase public awareness of the importance of consuming milk and yogurt to fulfill family nutrition. The simple manufacture of yogurt has inspired several community members to start a home-scale yogurt-making business. In addition, after replacing spare parts, cattle breeders can reuse automatic milking equipment to ensure the sanitation and hygiene of milk products.